Assessment of Potentially Inappropriate Medication in Elderly Patients at Basaveshwar Teaching and General Hospital - K.D, Praveen; K, Biradar; S.A, Hafiz; K, Karna; P.R, Neelkanta (Indian Journal of Pharmacy Practice)
The inappropriate prescribing (IP) is a major, public health problem in older people most often resulting from defective choice of medication by the prescriber. The present study was therefore entitled “Assessment of potentially inappropriate medication in elderly patients at our Basaweshwar Teaching and General Hospital. The Prospective observational study was carried out in the department of medicine the data was collected from the OPD cards of elderly patients.The total 150 patients was enrolled our study in which, 104 (69.3%) patients were males and 46 (30.6%) patients were female. It is observed that more number of patients were found in the age group of 65to74 is 94 (63.67%). The study shows that 57 numbers of (38%) prescriptions and 77 numbers of different drugs were reported to prescribe inappropriately. Among them Alprazolam (10.39%),Cimetidine(7.79%), Naproxen, Diazepam, Phenobarbitone (6.50%), Chlordiazepoxide, Ferrous sulphate, Hydroxyzine (5.20%), Cyproheptadine, Piroxicam, Cyclandelate, Chlordiazepoxide and Amitriptyline, Hyoscyamine, Amiodarone, Bisacodyl (3.89%), Nitrofurantoin, Digoxin, Fluoxetine, Orhenadrine, Ketorolac, Doxazosin & Nitrofurantoin (2.60%).The more number of inappropriateness was found in the age group of 65 to74 that is in 33 prescriptions (57.90%) followed by 75to84 that is 21 (36.84%). and very few cases was found in the age group ≥85 that is 03 (5.26%).
Keywords: Inappropriate prescribing; Elderly; Out patients